Solution-processable small molecule semiconductors based on pyrene-fused bisimidazole and influence of alkyl side-chain on the charge transport. Issue 73 (28th July 2016) - Wen, Hui; Gong, Xiaohui; Han, Pei; Lin, Baoping; Zhang, Lei; Ye, Shanghui; Sun, Ying; Zhang, Xueqin; Yang, Hong
Abstract : Soluble small molecule semiconductors based on pyrene-fused biimidazole and side-chain effects on the semiconducting properties. Abstract : To explore the potential of pyrene-fused biimidazole as a building block for soluble small molecule semiconductors, we designed and synthesizedPBI-L-Na andPBI-B-Na . Imidazole rings provided substitution positions for the solubilising groups at the K-region, however, DFT calculations revealed that the repulsive steric hindrance from the neighboring hydrogen atoms on pyrene forced alkyl side chains into a twisted conformation. Thus, side chains on this type of molecule exerted a prominent influence on the molecular packing and affected their optoelectronic properties intensively in the solid state.PBI-L-Na exhibited a more ordered packing of the large conjugated plane with a π–π stacking distance of 0.36 nm and showed a hole mobility up to 0.12 cm 2 V −1 s −1 . Bulkier branched chains provided better solubility but impeded molecular packing ofPBI-B-Na, thus giving a hole mobility of 4.6 × 10 −3 cm 2 V −1 s −1 .